Magnetic resonance imaging lesions are more severe and cartilage T2 relaxation time measurements are higher in isolated lateral compartment radiographic knee osteoarthritis than in isolated medial compartment disease – data from the Osteoarthritis Initiative. Issue 1 (January 2017) - Wise, B.L.; Niu, J.; Guermazi, A.; Liu, F.; Heilmeier, U.; Ku, E.; Lynch, J.A.; Zhang, Y.; Felson, D.T.; Kwoh, C.K.; Lane, N.E.
Summary: Objective: Isolated lateral compartment tibiofemoral radiographic osteoarthritis (IL-ROA) is an understudied form of knee osteoarthritis (OA). The objective of the present study was to characterize Magnetic Resonance Imaging (MRI) abnormalities and MR-T2 relaxation time measurements associated with IL-ROA and with isolated medial compartment ROA (IM-ROA) compared with knees without OA. Method: 200 case subjects with IL-ROA (Kellgren/Lawrence (K/L) grade ≥ 2 and joint space narrowing (JSN) > 0 in the lateral compartment but JSN = 0 in the medial compartment) were randomly selected from the Osteoarthritis Initiative baseline visit. 200 cases with IM-ROA and 200 controls were frequency matched to the IL-ROA cases. Cases and controls were analyzed for odds of having a subregion with >10% cartilage area affected, with ≥25% bone marrow lesions (BML), with meniscal tear or maceration, and for association with cartilage T2 values. Results: IL-ROA was more strongly associated with ipsilateral MRI knee pathologies than IM-ROA (IL-ROA: OR = 135.2 for size of cartilage lesion, 95% CI 42.7–427.4; OR = 145.4 for large size BML, 95% CI 41.5–509.5; OR = 176 for meniscal tears, 95% CI 59.8–517.7; IM-ROA: OR = 28.4 for size of cartilage lesion, 95% CI 14.7–54.7; OR = 38.1 for size of BML, 95% CI 12.7–114; OR = 37.0 for meniscal tears, 95% CI 12–113.6). Cartilage T2 values were higher in both tibial and medial femoral compartments in IL-ROA, but in IM-ROA were only significantly different from controls in the medial femur. Conclusion: IL-ROA knees show a greater prevalence and severity of MRI lesions and higher cartilage T2 values than IM-ROA knees compared with controls.